Stable Anxiety and Depression Trajectories in Late Adolescence for Oral Contraceptive Users - Doornweerd, Anne Marieke; Branje, Susan; Nelemans, Stefanie A.; Meeus, Wim H. J.; Montoya, Estrella R.; Engelhard, Iris M.; Baas, Joke M. P.; Gerritsen, Lotte (Frontiers in Psychiatry, 2022)
Background: The use of oral contraceptives (OCs) has been associated with increased incidences of anxiety and depression, for which adolescents seem to be particularly vulnerable. Rather than looking at singular outcomes, we examined whether OC use is associated with depressive and anxiety symptom trajectories from early adolescence into early adulthood. Materials and Methods: Data from 178 girls were drawn from the Research on Adolescent Development and Relationships (RADAR-Y) younger cohort study. We used assessments on 9 waves from age 13 until 24. Developmental trajectories of ratings on the Reynolds Adolescent Depression Scale (RADS-2) and the Screen for Child Anxiety Related Emotional Disorders (SCARED) were compared between never and ever users of OCs. Results: Never users showed increases in depressive and anxiety symptoms in late adolescence, whereas OC users showed a stable level of symptoms throughout adolescence. This effect remained after adjusting for baseline differences between groups in romantic relationships, sexual debut, educational level, smoking, drinking, and drug use. Age of OC use onset did not significantly predict symptom development. Conclusions: OC use in adolescence was related to an altered developmental trajectory of internalizing symptoms, in which OC users did not show an increase in depressive and anxiety symptoms in late adolescence, whereas never users did. The question remains whether this altered symptom trajectory can be considered a protective effect of OC use on psychopathology. Additional research is needed to improve our understanding of the long-term consequences of OC use on mental health.